Diagnoza partycypacji w kulturze w województwie podlaskim; Diagnosis of Participation in Culture in Podlaskie Voivodship - Jan Poleszczuk; Katarzyna Sztop-Rutkowska; Łukasz Kiszkiel; Andrzej Klimczuk; Rafał Julian Mejsak; Katarzyna Winiecka (Teatr Dramatyczny im. Aleksandra Węgierki w Białymstoku Fundacja Laboratorium Badań i Działań Społecznych ,,SocLab”, 2012)
"Celem diagnozy było: - przeprowadzenie badań dostarczających pełnej i rzetelnej wiedzy z zakresu potrzeb kulturalnych mieszkańców woj. podlaskiego; - wskazanie głównych barier uczestnictwa w kulturze wysokiej; - ilościowo-jakościowe określenie wizerunku instytucji kulturalnych, w tym Teatru Dramatycznego, i ocena ich działalności artystycznej; - zmierzenie poziomu kapitał kulturowego regionu na podstawie wskaźnika korzystania przez mieszkańców woj. podlaskiego z instytucji kulturalnych." – – The purpose of diagnosis was: conduct studies that provide full and accurate knowledge of the cultural needs of the residents of Podlasie Voivodship; identify the main barriers to participation in high culture; quantitative and qualitative definition of cultural institutions image, including the Drama Theatre, and the evaluation of their artistic activity; measure the region's cultural capital by an index of cultural institutions use by residents of Podlasie Voivodship.
Keywords: L38; A14; Z1; 300; Podlasie Region; Social Capital; High Culture; Cultural Capital; Artists; Cultural Institutions; Culture; Creativity; Mass Culture; Cultural Participation; Cultural Policy; Cultural Services; G.01.03.02 Central-Eastern Europe; N.06.02 Society and Social Change; W.28 Cultural Industries; N.08.03 Culture and the Arts; N.06.04 Special Sociologies and Issues in the Social Sciences; N.07 Psychology; N.04.03.05 Cultural; Educational; and Science Policy